Association of Medication Access Difficulty and COVID‐19–Related Distress With Disease Flares in Rheumatology Patients During the COVID‐19 Pandemic. Issue 8 (5th July 2021) - Maldonado, Dalynah; Tu, Emilee; Mahmood, Shereen N.; Wahezi, Dawn M.; Darapaneni, Ruchika; Sima, Niloofar; Curiel‐Duran, Laura; Pattison, Lindsay M.; Gabbay, Vilma; Bauman, Laurie J.; Broder, Anna; Rubinstein, Tamar B.
Abstract : Objective: Due to concerns of infection and medication disruptions during the COVID‐19 pandemic, rheumatology patients at the pandemic epicenter were at risk of distress and poor health outcomes. We sought to investigate medication disruptions and COVID‐19–related distress in the Bronx, New York shortly after the peak of the pandemic and determine whether factors related to the pandemic were associated with flares, disease activity, and overall health. Methods: In the month following the epidemic peak, we surveyed adult patients and parents of pediatric patients from rheumatology clinics in the Bronx regarding medication access, medication interruptions, COVID‐19 infection, COVID‐19 hospitalization, and COVID‐19–related distress. We examined which factors were associated with patient‐reported flares, disease activity, and overall health scores in regression models accounting for sociodemographic characteristics and rheumatologic disease type. Results: Of the 1, 692 patients and parents of pediatric patients that were contacted, 361 (21%) responded; 16% reported medication access difficulty, 14% reported medication interruptions, and 41% reported experiencing flare(s). In a multivariable logistic regression model, medication access difficulty was associated with increased odds of flare (odds ratio [OR] 4.0 [95% confidence interval (95% CI) 1.5, 10.4]; P = 0.005), as was high COVID‐19–related distress (OR 2.4 [95% CI 1.2, 4.6]; P = 0.01). In multivariable linear regression models, medication access difficulty and high COVID‐19–related distress were associated with worse disease activity scores, and high COVID‐19–related distress was associated with worse health scores. Conclusion: Medication access difficulties and flares were common among rheumatology patients from the Bronx, New York in the month following the peak of the epidemic. Medication access difficulty and COVID‐19–related distress were highly associated with flare and disease activity. COVID‐19–related distress was associated with overall health scores.